Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia